Le modèle Universal Instructional Design au service de l’égalité des chances dans les universités canadiennes : apports, enjeux et défis - Ruth Philion; Christine Lebel; Louise M. Bélair (Éducation et Socialisation)
The early 60s is witness to the democratization of universities as access is greatly expanded. With this massification two new student profiles emerge. The first includes students who are more or less prepared to meet university requirements, some of whom face serious difficulties in adaptation which, in the end, translates into a failure and drop-out rate of 25 and 30 % for first and second year students. The second group consists of students who experience a wide range of functional limitations that universities have an obligation to provide accommodations for. While a great variety of supports are put into place inside and outside the classroom to reduce the failure and drop-out rate of the first group of students—without much success—the second group, benefits from accommodations that contribute significantly to their academic success. Recognizing that both groups have comparable needs, American universities and more recently, Canadian universities, have put into place guidelines driven by the Universal Instructional Design which is decidedly inclusive. Although U.I.D.’s founding pedagogical principles are commendable, its application makes strong demands on universities and forces them to redefine their current practices and as well, to clarify what their educational mission truly is. This article presents issues associated with this approach in consideration of a context where program objectives continue to lack clarity.